Silk fibroin blood vessel embolism agent loaded with polyhydroxy phenolic compound and preparation method of silk fibroin blood vessel embolism agent

By self-assemblying the polyhydroxyphenol compounds and silk fibroin, the silk fibroin vascular embolizers loaded with polyhydroxyphenol compounds are solved, and the existing vascular embolizers have poor biocompatibility and unstable embolization effect are solved. Problem, rapid hemostasis and tumor-assisted treatment have been achieved, and good biocompatibility and degradability.

CN119405874AActive Publication Date: 2025-02-11NANJING UNIV OF TRADITIONAL CHINESE MEDICINE
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411518174.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-01-11
Filing Date
2024-10-29
Publication Date
2025-02-11
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

Existing vascular embolization agents have problems such as poor biocompatibility, unstable embolization effect, and may trigger inflammatory responses, and it is difficult to achieve precise embolization of tumor blood vessels.

Method used

The polyhydroxyphenol compound-loaded silk fibroin complex is prepared by self-assemblying the polyhydroxyphenol compound and the silk fibroin compound to form a silk fibroin vascular embolist supported by the polyhydroxyphenol compound. The composite is processed by a β-sheet conformation transformation process, and is prepared by emulsification and dispersion method, phase separation and coagulation method, etc.

Benefits of technology

This embolization agent can quickly solidify in the blood vessels, effectively block blood flow, achieve rapid hemostasis, and can be combined with anti-tumor drugs for auxiliary treatment, significantly improving the effectiveness of tumor vascular embolization treatment. At the same time, it has good biocompatibility, degradability and mechanical properties, reducing damage to surrounding tissues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119405874A_ABST
    Figure CN119405874A_ABST
Patent Text Reader

Abstract

The silk fibroin vascular embolization agent loaded with the polyhydroxy phenolic compound is prepared from a silk fibroin compound loaded with the polyhydroxy phenolic compound, and the silk fibroin compound loaded with the polyhydroxy phenolic compound is prepared from the polyhydroxy phenolic compound and silk fibroin in a self-assembly mode. The silk fibroin is treated by a beta folding conformation transformation process, and the feeding mass ratio of the polyhydroxy phenolic compound to the silk fibroin is 1t; 1: 1; the vascular embolization agent is prepared by one of an emulsification dispersion method, a phase separation coagulation method, a supercritical fluid technology, an electrostatic adsorption method and a dry granulation method. The vascular embolism agent has good biocompatibility and degradability, can effectively block blood flow and realize rapid hemostasis, and can be used for tumor vascular embolism treatment. Through an innovative self-assembly strategy, the mechanical property of the silk fibroin microspheres is remarkably improved. Compared with the traditional hemostatic material, the hemostatic material has higher settling velocity and higher hemostatic efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of materials, and in particular relates to a silk fibroin vascular embolic agent loaded with polyhydroxyphenol compounds and a preparation method thereof. Background Art

[0002] Hemostasis and tumor treatment are two important and challenging directions in the medical field. In the case of trauma, surgery or certain disease states, improper hemostasis may lead to serious health problems or even death. Similarly, in tumor treatment, how to effectively block the blood supply of the tumor and limit its growth and metastasis is the key to improving the treatment effect. As an effective treatment method, vascular embolic agents are widely used in hemostasis and tumor vascular embolization therapy. However, existing embolic agents have certain limitations, such as poor biocompatibility, unstable embolization effect, and possible inflammatory response. Therefore, the research and development of new and efficient vascular embolic agents is of great clinical significance.

[0003] Traditional hemostatic methods include physical means such as direct compression, suturing, the use of tourniquets, and the application of hemostatic drugs. Physical means may not be effective or applicable in some cases, and hemostatic drugs may have systemic side effects. In recent years, with the development of materials science, various new hemostatic materials have emerged, such as mineral-based materials, polymer-based materials, and bio-based materials. These materials have made certain progress in improving the efficiency of hemostasis, but there are still some problems, such as slow hemostasis, possible infection, and possible toxicity of degradation products. Tumor vascular embolization therapy blocks tumor blood vessels and cuts off the nutrient supply of tumors, thereby achieving the purpose of controlling tumor growth and metastasis. Commonly used embolic agents include gelatin sponges, polyvinyl alcohol particles, metal coils, etc. These materials have achieved certain clinical efficacy, but there are problems such as poor biocompatibility, non-persistent embolization effects, and possible inflammation. In addition, how to achieve precise embolization of tumor blood vessels and avoid damage to normal tissues is also a hot spot and difficulty in current research.

[0004] Silk fibroin has shown significant application potential in vascular embolization therapy due to its excellent biocompatibility, biodegradability and excellent mechanical properties. This natural protein is derived from silk and has low immunogenicity and good biostability, which can minimize the patient's immune response when used in vivo. In addition, the degradation products of silk fibroin can be naturally cleared by the human body, reducing the risk of complications that may be caused by long-term implantation of materials. By finely regulating the self-assembly process of silk fibroin and natural polyhydroxy-classified compounds, a composite embolic agent with good coagulation activity and efficient embolization ability can be prepared. This self-assembly technology not only improves the mechanical properties and bioactivity of the material, but also ensures the consistency of product size and shape, thereby reducing potential damage to surrounding normal tissues.

[0005] Although the self-assembled embolic agents of silk fibroin and natural polyhydroxy compounds have significant advantages, they still face technical challenges, such as precise control of self-assembly conditions, optimization of material ratios, and verification of long-term biosafety and effectiveness. The present invention aims to solve the limitations of existing technologies through innovative self-assembly methods and provide a safer and more effective vascular embolization solution. Summary of the invention

[0006] The purpose of the present invention is to address the problem of multiple side effects of existing vascular embolic agents, and to provide a silk fibroin vascular embolic agent loaded with polyhydroxyphenol compounds, wherein the vascular embolic agent is prepared from a silk fibroin protein complex loaded with polyhydroxyphenol compounds, wherein the silk fibroin protein complex loaded with polyhydroxyphenol compounds is prepared by self-assembly of polyhydroxyphenol compounds and silk fibroin, the silk fibroin is treated by a β-folding conformational transformation process, and the feed ratio of the polyhydroxyphenol compound to the silk fibroin is a mass ratio of <1:1; the vascular embolic agent is prepared by one of an emulsification dispersion method, a phase separation coagulation method, a supercritical fluid technology, an electrostatic adsorption method, and a dry granulation method.

[0007] As a further improvement, the polyhydroxyphenol compound is selected from one or more of resveratrol, quercetin, baicalein, kaempferol, lignans, curcumin, ellagic acid, chlorogenic acid, ferulic acid, caffeic acid, syringic acid, sinapinic acid, rutin, myricetin, magnolic acid, fisetin, puerarin, rhein, honeysuckle glycoside, proanthocyanidins, p-coumaric acid, vanillic acid, hesperidin, naringenin, luteolin, genistein, rhein, oleanolic acid, epigallocatechin gallate, acacia glycoside, tea polyphenols, epigallocatechin, salvianolic acid, gallic acid, pyrogallol, catechins, and tannic acid.

[0008] As a further improvement, the polyhydroxyphenol compound is a poorly soluble polyhydroxyphenol compound, preferably one or more selected from resveratrol, quercetin, baicalein, kaempferol, lignans, curcumin, ellagic acid, chlorogenic acid, ferulic acid, caffeic acid, syringic acid, sinapinic acid, rutin, myricetin, magnolic acid, fisetin, puerarin, rhein, honeysuckle, proanthocyanidins, p-coumaric acid, vanillic acid, hesperidin, naringenin, luteolin, genistein, rhein, oleanolic acid, and epigallocatechin gallate; ellagic acid is most preferred.

[0009] As a further preferred embodiment, the feed ratio of ellagic acid to silk fibroin is 1:2 to 1:16 by mass, and most preferably 1:4.

[0010] The present invention also provides a method for preparing the above-mentioned silk fibroin vascular embolic agent, comprising three steps of silk fibroin conformational transformation, self-assembly with a polyhydroxyphenol compound, and preparation of a vascular embolic agent: Step (1): preparing a silk fibroin solution by a process of transforming the silk fibroin conformation from an α-helix to a β-folded conformation, wherein the conformational change can be achieved by chemical or physical methods, wherein the chemical method comprises promoting the transformation by polyols, polylactic acid, metal ions, pH or hydroxypropyl methylcellulose, and the physical method comprises promoting the transformation by high temperature, hydration and pressure, ultra-low temperature placement, freeze drying, shear force, ultrasound, vortex , laser irradiation, and high-pressure carbon dioxide treatment to promote the transformation; step (2): after the polyhydroxyphenol compound is dissolved or suspended, it is mixed with the silk protein solution obtained in step (1) and stirred to cause self-assembly to obtain a silk protein complex loaded with polyhydroxyphenol compounds; step (3): the silk protein complex loaded with polyhydroxyphenol compounds obtained in step (2) is prepared by one of the following methods: emulsification dispersion method, phase separation coagulation method, supercritical fluid technology, electrostatic adsorption method, and dry granulation method to form a silk protein vascular embolic agent loaded with polyhydroxyphenol compounds.

[0011] As a further improvement, the step (1) uses a polyol to promote the transformation of the β-folding conformation of silk fibroin. As a further improvement, the polyol is ethanol.

[0012] Beneficial effects: The embolic agent provided by the present invention can be rapidly solidified and formed in the blood vessel, effectively blocking the blood flow and achieving the effect of rapid hemostasis. More importantly, the embolic agent can also be combined with suitable anti-tumor drugs for adjuvant therapy, thereby significantly improving the effectiveness of tumor vascular embolization therapy, and has the effect of adjuvant tumor therapy. At the same time, it has the significant advantages of simple preparation process, high production efficiency, easy industrial production and environmental protection. Through the innovative mixed polyhydroxyphenol compound strategy, the mechanical properties of silk protein microspheres are significantly improved, and biocompatibility and degradability are maintained. In addition, the embolic agent has an ideal degradation cycle, can provide effective support during treatment, and avoid the risks brought by long-term retention. Compared with traditional hemostatic materials, silk protein complexes show faster sedimentation rate and higher hemostatic efficiency, and at the same time have excellent biosafety, no cytotoxicity, no hemolytic reaction, and can be naturally degraded in the body, providing a fast, efficient and safe hemostatic solution for clinical emergency and surgical operations. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] The present invention will be further described below in conjunction with the accompanying drawings:

[0014] Figure 1 Fourier transform infrared spectroscopy (FTIR).

[0015] Figure 2 to Figure 4Comparison of blood viscosity (n=3), Figure A in each figure: *, compared with the blank control group, *P<0.05, **P<0.01, ***P<0.001; #, compared with the β-SF-EA group, #P<0.05, ##P<0.01, ###P<0.001. Compared with the β-SF-polyhydroxyphenol compound group, *P<0.05, **P<0.01, ***P<0.001, for example: compared with the β-SF-EA group, *P<0.05,

[0016] **P<0.01,***P<0.001.

[0017] Figure 5 Comparison of coagulation time (n=3), *, compared with the β-SF-EA group, *P<0.05, **P<0.01, ***P<0.001. Figure 6 Comparison of drug loading (n=3). *, compared with β-SF-EA group, *P<0.05, **P<0.01, ***P<0.001; ND means Not Detected.

[0018] Figure 7-Figure 8 Comparison of drug loading (n=3). *, compared with the water group, *P<0.05, **P<0.01, ***P<0.001.

[0019] Fig. 9 Fourier transform infrared spectroscopy (FTIR) analysis showed that the physical mixture of EA and β-SF was 1:1 (w / w).

[0020] Fig.10 Molecular docking diagram. L74 represents Leu (leucine) at position 74, and D27 represents Asp (aspartic acid) at position 27.

[0021] Fig.11 Characterization: (A) FTIR spectroscopy, (B) XRD, (C) TG, (D) 1H NMR.

[0022] Fig.12 Blood adsorption experiment. Among them, a is blank, b is β-SF, c is EA, d is Yunnan Baiyao, e is tranexamic acid, and f is β-SF-EA. Fig.13 Same as in China.

[0023] Fig.13 Diagram of the test tube tilt coagulation experiment.

[0024] Fig.14 Blood coagulation index BCI graph (n=3).

[0025] Fig.15Rat tail amputation experiment. Figure A shows the bleeding of rats immediately after tail amputation with drug powder, and Figure B shows the bleeding time after tail amputation; *, compared with the β-SF-EA group, *P<0.05, **P<0.01, ***P<0.001.

[0026] Fig.16 Bleeding time of rat liver and femoral artery (n=3). *, compared with β-SF-EA group, *P<0.05, **P<0.01, ***P<0.001.

[0027] Fig.17 Relative cell proliferation rate of LO2 cells and L929 cells after incubation with drugs for 48 hours (n=6).

[0028] Fig.18 In vitro degradation of β-SF-EA (n=3).

[0029] Fig.19 Swelling ratio determination (n=3).

[0030] Fig. 20 Degradation rate determination (n=3).

[0031] Fig.21 Rabbit kidney injury and bleeding experiment (n=3).

[0032] Fig. 22 Rabbit ear tumor experiment (n=3), Fig.21 , 22 Compared with the autologous thrombus group, *P<0.05, **P<0.01, ***P<0.001. DETAILED DESCRIPTION

[0033] Example 1 Preparation of polyhydroxyphenol compound-loaded silk fibroin complex (β-SF-polyhydroxyphenol compound)

[0034] Step (1) Transformation of the β-folded conformation of silk fibroin: dilute silk fibroin (SF) with water by 5 to 10 times and then slowly pour it into an excess of vigorously stirred organic solvent, stir for 2 to 4 hours to complete the transformation of the β-folded conformation, remove the liquid portion by mechanical separation methods such as filtration, centrifugation, and membrane filtration, and repeatedly wash the remaining portion and then freeze-dry to obtain β-folded silk fibroin (β-SF), wherein the organic solvent is selected from methanol, ethanol, propylene glycol, butylene glycol, etc., preferably ethanol; the mechanical separation method is preferably high-speed centrifugation, such as high-speed centrifugation at 10,000 rpm for 15 to 20 minutes.

[0035] Fourier transform infrared spectroscopy (FTIR) analysis: 5% of the sample was mixed with 95% KBr and ground into fine powder, and then scanned by transmission using a FTIR spectrometer (Nicolet is5). Each spectrum was obtained in transmission mode (ten scans) with a resolution of 4 cm -1 , the spectral range is 4000-500cm -1 The FTIR spectrum of the relatively high level of β-sheet structure is at 1615-1640 cm -1 、1510-1525cm -1 The FTIR spectrum of SF in its natural state shows a sharp peak at 1640-1660 cm -1 、1535-1542cm -1 A sharp peak is shown at α-SF. Figure 1 The results show that the characteristic peak of natural α-SF is 1642 cm -1 and 1535cm -1 The characteristic peak of SF after treatment in step (1) is 1620 cm -1 and 1517cm -1 , it can be seen that SF has completed the conformational transition of β-folding and become β-SF.

[0036] Step (2) Self-assembly of polyhydroxyphenol compounds and silk fibroin: The β-SF obtained in step (1) is prepared into a suspension with water and placed in a magnetic stirrer at 500-2000 rpm; the polyhydroxyphenol compound is dissolved or suspended with a solvent, wherein water is used as a solvent for water-soluble polyhydroxyphenol compounds and water or an organic solvent such as ethanol, propylene glycol, or butylene glycol is used as a solvent for poorly soluble polyhydroxyphenol compounds; the prepared solution or suspension is added dropwise to the β-SF suspension, and the mixture is stirred for 12-48 hours to obtain a silk fibroin complex loaded with polyhydroxyphenol compounds.

[0037] The polyhydroxyphenol compound is selected from water-insoluble polyhydroxyphenol compounds, including ellagic acid (EA), resveratrol (RES), quercetin (QUE), baicalein (BAE), kaempferol (KAE), lignan (Lignan), curcumin (CUR), chlorogenic acid (CGA), ferulic acid (FA), caffeic acid (CFA), syringic acid (SA), sinapic acid (Sinapic Acid), rutin (RUT), myricetin (MYR), magnolic acid (Magnolol Acid, MA), Fisetin (FIS), Puerarin (PUE), Rhein (RHE), Lonicerin (Lon), Proanthocyanidins (PC), p-Coumaric Acid (p-CA), Vanillic Acid (VA), Hesperetin (Hes), Naringenin (NAR), Luteolin (Luteolin), Genistein (Gen), Emodin (Emo), Oleanolic Acid (Ola), Danshensu (DS), Epigallocatechin gallate (EGCG); Water-soluble polyhydroxyphenol compounds, including Gallic Acid (GA), Pyrogallic Acid (PGA), Acid, PA), catechin (C), tannic acid (TA), tea polyphenols (TP), acacia glycoside (Acaciin), epigallocatechin (EGC), etc.

[0038] Example 2 Preparation of Silk Fibroin Composites Loaded with Polyhydroxyphenol Compounds

[0039] The difference from Example 1 is that the organic solvent in step (1) is ethanol, and the mechanical separation method is high-speed centrifugation at 10000rpm for 15-20min. In step (2), equal amounts of polyhydroxyphenol compounds and silk fibroin are added, and in the preparation of the polyhydroxyphenol compound suspension, water is used as a solvent for water-soluble polyhydroxyphenol compounds, and water or an organic solvent is used as a solvent for sparingly soluble polyhydroxyphenol compounds, and the mechanical separation method is to take the precipitate after high-speed or ultra-high-speed centrifugation. Add step (3) of drying into powder: the solution obtained in step (2) is dried into powder after removing liquid by mechanical separation methods such as suction filtration, centrifugation, membrane, sedimentation, etc., or a spray dryer or other drying equipment is used to powder in one step, so as to obtain a silk fibroin complex loaded with polyhydroxyphenol compounds; the mechanical separation method is preferably to take the precipitate after high-speed or ultra-high-speed centrifugation.

[0040] Using poorly soluble polyhydroxyphenol compounds as raw materials: ellagic acid-silk protein complex (β-SF-EA), resveratrol-silk protein complex (β-SF-RES), quercetin-silk protein complex (β-SF-QUE), baicalin-silk protein complex (β-SF-BAE), kaempferol-silk protein complex (β-SF-KAE), lignan-silk protein complex (β-SF-Lignan), curcumin-silk protein complex (β-SF-CUR), chlorogenic acid-silk protein complex (β-SF-CGA), ferulic acid-silk protein complex (β-SF-FA), caffeic acid-silk protein complex (β-SF-CFA), syringic acid-silk protein complex (β-SF-SA), sinapinic acid-silk protein complex (β-SF-Sinapic acid-silk protein complex (β-SF-Sinapic acid-silk protein complex) were prepared. Acid), rutin-silk protein complex (β-SF-RUT), myricetin-silk protein complex (β-SF-MYR), magnoliic acid-silk protein complex (β-SF-MA), fisetin-silk protein complex (β-SF-FIS), puerarin-silk protein complex (β-SF-PUE), rhein-silk protein complex (β-SF-RHE), honeysuckle glycoside-silk protein complex (β-SF-Lon), proanthocyanidin-silk protein complex (β-SF-PC), p-coumaric acid-silk protein complex (β-SF-p-CA), vanillic acid-silk protein complex (β-SF-VA), hesperidin-silk protein complex (β-SF-Hes), naringenin-silk protein complex (β-SF-NAR), luteolin-silk protein complex (β-SF-Lut), genistein -Silk fibroin complex (β-SF-Gen), rhubarb-silk fibroin complex (β-SF-Emo), oleanolic acid-silk fibroin complex (β-SF-Ola), salvianol-silk fibroin complex (β-SF-DS), epigallocatechin gallate-silk fibroin complex (β-SF-EGCG); using water-soluble polyhydroxyphenol compounds as raw materials, gallic acid-silk fibroin complex (β-SF-GA), pyrogallol-silk fibroin complex (β-SF-PA), catechin-silk fibroin complex (β-SF-C), tannic acid-silk fibroin complex (β-SF-TA), acacia glycoside-silk fibroin complex (β-SF-Acaciin), epigallocatechin-silk fibroin complex (β-SF-EGC), tea polyphenols-silk fibroin complex (β-SF-TP) were prepared.

[0041] Example 3 Investigation of blood coagulation effect

[0042] The obtained β-SF-polyhydroxyphenol compounds were prepared into 2 mg / mL test solution with normal saline for investigation of coagulation effect: blood was collected from the abdominal aorta of New Zealand white rabbits and placed in a sodium heparin anticoagulant tube, 2 mL of the test solution was added to the tube, normal saline was used as a control, mixed well, incubated at 37°C for 15 min, and then the whole blood viscosity was detected with an automatic blood rheometer (all operations were completed within 2 h after blood collection).

[0043] Whole blood viscosity is the result of friction between blood cells and plasma protein molecules when blood flows, and is the most important indicator in blood rheology. When blood viscosity increases, it means that blood flow is obstructed, while the deformability of red blood cells decreases and aggregation increases, the flow of blood into microvessels and capillaries decreases, and the passing capacity decreases. Figures 2 to 4 The results showed that the silk fibroin complex loaded with polyhydroxyphenol compounds (β-SF-polyhydroxyphenol compounds) could significantly increase the whole blood viscosity compared with the blank group (P<0.05), and was significantly better than the effect of β-SF and the original compound itself (P<0.05), indicating that the formation of the complex can significantly enhance the coagulation effect; and overall, the effect of the self-assembled complex of silk fibroin and insoluble polyhydroxyphenol compounds was better than its self-assembled complex with water-soluble polyhydroxyphenol compounds.

[0044] Weigh 0.1g of the drug powder to be tested and place it in a 1.5mL centrifuge tube. At the same time, measure 0.5mL of anticoagulated blood and add it to the centrifuge tubes containing different drugs. Place them vertically on the laboratory workbench and start timing. After 30s, rotate the inverted centrifuge tube to observe whether the blood flows. Repeat the operation until the anticoagulated blood cannot flow, stop timing, and record it as the coagulation time. Figure 5 The results showed that Figures 2 to 4 The results show a similar trend.

[0045] Among all the complexes, β-SF-EA has the best coagulation effect. This may be related to the multiple hydrogen bonds and planar structure of EA. On the one hand, the existence of multiple hydrogen bonds increases the synergistic effect between hydrogen bonds and further improves the stability of hydrogen bonds; on the other hand, ellagic acid has a symmetrical catechol structure and a planar structure, which can form intramolecular and intermolecular hydrogen bonds, thereby enhancing the rigidity of the complex molecules. This stable molecular structure can reduce the dynamic changes of the molecules, thereby indirectly improving the stability of the intermolecular hydrogen bonds.

[0046] Example 4 Preparation of polyhydroxyphenol compound-silk fibroin complex (α-SF-polyhydroxyphenol compound)

[0047] The difference from Example 2 is that step (1) is deleted, and in step (2), β-SF is replaced by untreated SF, i.e., SF with a natural α-helical conformation. In step (2), equal amounts of polyhydroxyphenol compounds and silk fibroin are added to prepare a polyhydroxyphenol compound-α-silk fibroin complex, which is called α-SF-polyhydroxyphenol compound.

[0048] Example 5 Preparation of polyhydroxyphenol compound-silk fibroin complex (SH-SF-polyhydroxyphenol compound)

[0049] The difference from Example 2 is that the following method is used in step (1): dissolving silk fibroin in a solution containing three ( The SF solution treated with a reduction reaction at room temperature for 5 minutes is placed in an aqueous solution of (hydroxyethyl)phosphine hydrochloride to obtain a SF solution with a concentration of 1.0-5.0wt% treated with a reduction reaction. The rest is the same as the method in Example 2, wherein in step (2), equal amounts of polyhydroxyphenol compounds and silk fibroin are added to prepare a polyhydroxyphenol compound-silk fibroin complex called SH-SF-polyhydroxyphenol compound. This method uses a method of destroying disulfide bonds to expose hydrophobic amino acids to bind polyhydroxyphenol compounds such as ellagic acid.

[0050] Example 6 Self-assembly performance study

[0051] The polyhydroxyphenol compound uses ellagic acid as a model drug, and three ellagic acid-silk protein complexes are prepared according to the steps in Examples 2, 4, and 5, wherein the solvent of EA is water, namely β-SF-EA, α-SF-EA, and SH-SF-EA. The assembly efficiency is evaluated by drug loading and encapsulation efficiency, which are calculated by formula 1) and formula 2) respectively, wherein the "amount of EA in the silk protein complex" on the molecule is calculated by the difference method, that is, the amount of EA is subtracted from the free amount after co-incubation with SF. The EA content is analyzed by high performance liquid chromatography (HPLC), and the chromatographic column uses a Hedera C18 column, the mobile phase is acetonitrile: water = 20:80 (v / v), the flow rate is 1.0 mL / min, the detection wavelength is 254 nm, the injection volume is 10 μL, and the spectrum acquisition time is 15 min. The drug loading and encapsulation efficiency are calculated using the following formula:

[0052] Drug loading = amount of EA in silk fibroin complex / total amount of SF and EA (Formula 1)

[0053] Encapsulation efficiency = amount of EA in silk protein complex / EA dosage (Formula 2)

[0054] Depend on Figure 6The results show that the drug loading is: β-SF-EA>SH-SF-EA>>α-SF-EA, among which the drug loading of β-SF-EA reaches 9.6%, while EA is almost undetectable in α-SF-EA, indicating that the efficiency of self-assembly of α-helical silk protein and ellagic acid is very low, highlighting the necessity of conformational flipping of silk protein; SH-SF-EA uses the destruction of disulfide bonds in silk protein molecules to expose its hydrophobic amino acids, thereby completing self-assembly with ellagic acid, but the drug loading is only 4.5%, much lower than β-SF-EA (P<0.001).

[0055] Example 7 Study on the effect of solvent on EA drug loading

[0056] Ellagic acid was used as a model drug for the polyhydroxyphenol compound, and β-SF-EA was prepared by the steps in Example 2. In step (2), water, ethanol, propylene glycol, butylene glycol, etc. were used as solvents to prepare the polyhydroxyphenol compound suspension. If an organic solvent was used as the suspension solvent, the final concentration of the organic solvent in the solution obtained after the polyhydroxyphenol compound suspension was incubated with β-SF was 10%. The drug loading capacity was investigated by the method in Example 6. Figure 7 The results showed that the addition of organic solvents effectively increased the drug loading of ellagic acid, among which propylene glycol > butylene glycol > ethanol > water. The drug loading was the highest when propylene glycol was used, reaching 19.57±1.01%.

[0057] Next, the effect of propylene glycol concentration on the drug loading of EA was investigated. In step (2), propylene glycol was used as a solvent to prepare EA suspension. After incubation with β-SF, the final concentrations of propylene glycol in the obtained solutions were 0%, 5%, 10%, 15%, and 20%, respectively. Figure 8 The results showed that the drug loading of the propylene glycol aqueous solution group was better than that of the water group, among which the 10% propylene glycol aqueous solution group had the best effect, with a drug loading of 19.57±1.01%.

[0058] Example 8 Investigation of different EA:SF feed ratios

[0059] Ellagic acid was used as a model drug for polyhydroxyphenol compounds, and β-SF-EA was prepared using the steps in Example 2, wherein step (2) used propylene glycol as a solvent to prepare an EA suspension, and the final concentration of propylene glycol in the solution obtained after co-incubation with β-SF was 10%; at the same time, the feed ratio of EA to β-SF was controlled to be EA:β-SF=1:0.5, 1:1, 1:2, 1:4, 1:8, 1:12, 1:16 (w / w). As shown in Table 1, the drug loading and encapsulation efficiency of EA were almost not observed for EA:β-SF=1:0.5 and 1:1, while they could be observed for other groups; at the same time, the samples of each group were analyzed by Fourier transform infrared spectroscopy using the method in Example 1 ( Fig. 9), it can be seen that the EA hydroxyl peak (3471cm) was observed in the EA:β-SF=1:2, 1:4, 1:8, 1:12, 1:16 (w / w) groups. -1 ) disappeared, indicating that EA and β-SF have completed hydrogen bonding and self-assembled successfully, but the EA:β-SF=1:0.5, 1:1 group and its physical mixed group still have EA hydroxyl peaks, and the self-assembly of the two molecules cannot be achieved. The above results show that the self-assembly of β-SF and EA can only be achieved when the feed ratio EA:β-SF<1:1 (w / w), among which EA:β-SF=1:4 can achieve the maximum value of EA drug loading and encapsulation efficiency (Table 1), which is called the optimal feed ratio.

[0060] The method in Example 3 was further used to investigate the effects of different EA:β-SF feed ratios on whole blood viscosity. The results in Table 2 showed that the EA:β-SF<1:1 groups significantly increased whole blood viscosity at low, medium, and high shear rates compared with the normal saline group (P<0.5), and were higher than the EA and β-SF groups (P<0.5), indicating that the β-SF-EA prepared with an EA:β-SF<1:1 feed ratio had significant coagulation efficacy, and that EA and β-SF enhanced synergistically; among them, EA:β-SF=1:4 had the best coagulation effect.

[0061] In summary, the preparation process of β-SF-EA is to use β-folded SF for preparation, and the feed ratio EA:β-SF<1:1 (w / w), and the specific steps are shown in Example 1; wherein the optimal process is EA:β-SF=1:4 (w / w), and the ellagic acid in step (2) is used as a solvent to prepare a suspension, and the final concentration of propylene glycol in the obtained solution after incubation with SF is 10%. The self-assembly of EA and β-SF cannot be achieved without the transformation of the β-folded conformation of SF or the feed ratio EA:β-SF≥1:1. When EA:β-SF=1:2 (w / w), the drug loading and encapsulation efficiency are both low, indicating that although the self-assembly of EA and β-SF can be achieved at this time, the loss is large.

[0062] Table 1 Effect of the feed ratio of β-SF to EA on drug loading and encapsulation efficiency (n=3)

[0063]

[0064] ND means Not Detected.

[0065] Table 2 Effect of different EA:β-SF feed ratios on whole blood viscosity (n=3)

[0066]

[0067]

[0068] *: Compared with the normal saline group, *P<0.05, **P<0.01, ***P<0.001; #: Compared with the EA:β-SF=1:4 group, #P<0.05, ##P<0.01, ###P<0.001.

[0069] Example 9 Molecular docking of silk fibroin complex

[0070] Computer simulation study on the binding mode of ellagic acid and silk fibroin was performed. After obtaining the silk fibroin heavy chain crystal structure from PDB bank (PDB number: 3UA0), due to the lack of previous studies on the binding mode, we In 2018, the SiteMap module was used to predict the binding sites reasonably. After the silk protein crystal structure was hydrogenated and irrelevant ions were removed, the ellagic acid small molecule was converted into a 3D conformation via the LigPrep module, outputting up to 32 isomers, and finally Glideextra precision (XP) was used to output 20 binding poses. Fig.10 As shown, after the two phenolic hydroxyl groups in the ellagic acid small molecule form hydrogen bonds with L74, they also need to form hydrogen bonds with D27 on another heavy chain, indicating that the continued formation of hydrogen bonds with the other two highly symmetrical hydroxyl groups in ellagic acid can achieve stable binding. In addition, since the heavy chains in the silk fibroin maintain a highly similar β-folded secondary structure, there may not be enough hydrophobic interaction between the ellagic acid small molecule and the two heavy chain proteins to maintain stability. It is reasonable to speculate that the ellagic acid small molecule will be bound and wrapped with at least three to four heavy chain proteins to achieve stable binding. The molecular docking results explain the molecular mechanism of the experimental results of "EA:β-SF<1:1 (w / w) can achieve self-assembly of β-SF and EA" in Example 8.

[0071] The tested samples in Examples 10 to 14 were prepared using the optimal process to obtain β-SF-EA.

[0072] Example 10 Characterization of Silk Fibroin Composites Loaded with Polyhydroxyphenol Compounds

[0073] FT-IR confirmed the self-assembly of EA and β-SF ( Fig.10 A): EA hydroxyl peak (3471 cm -1 ) indicates that EA and β-SF may self-assemble through intermolecular hydrogen bonds. X-ray diffraction (XRD) ( Fig.10The characteristic peaks of EA in B) weaken or disappear after combining with silk fibroin, indicating that this is not a simple physical mixture, but a new crystal phase formed by interaction, confirming the FT-IR results; at the same time, the change of crystal form is seen, β-SF shows broad diffraction peaks, indicating that they are amorphous macromolecules; EA shows many strong diffraction peaks, indicating that it is in a crystalline state; after β-SF and EA self-assemble, the peak intensity of EA decreases significantly, and it can be judged that β-SF-EA is mainly amorphous macromolecules.

[0074] Thermogravimetric (TG) curves were evaluated and divided into three stages ( Fig.11 C). In the first stage, from room temperature to 120 ° C, the weight loss is about 6.1%, which is mainly due to the evaporation and desorption of adsorbed water; in the second stage, the temperature is between 150 ° C and 450 ° C, which corresponds to the decomposition of silk protein molecular chains, the decomposition of amino acid residue side chains and the cleavage of peptide bonds, among which the silk I crystal structure (α-helix and random coil) degrades at 250 ° C, and the silk II crystal structure (β-sheet) degrades at 260 ° C; β-SF shows a major degradation peak at 260 ° C, and a stable β-fold conformation is formed on the surface; Interestingly, the main degradation peak of β-SF-EA shifts to 280 ° C, indicating that the silk II crystal structure is more stable, which may be due to the strong interaction between EA and protein during the self-assembly process, thereby improving the stability of the complex. In order to determine the optimal amount of EA incorporated into β-SF, proton nuclear magnetic resonance (1H NMR) ( Fig.11 D): In β-SF-EA, the peak associated with EA was significantly attenuated (<0.007), confirming that EA binds to β-SF via catechol hydrogen, further demonstrating their association.

[0075] Example 11 Investigation of blood coagulation effect

[0076] (1) Plasma sample processing

[0077] New Zealand white rabbits were fed adaptively for one week and fasted the night before the experiment. 1% sodium pentobarbital was used at 3 mL kg -1 The anesthetic dose is injected intraperitoneally. After anesthesia, blood is collected from the abdominal aorta using a 5 mL sodium heparin anticoagulant tube. After blood collection, the blood and anticoagulant must be fully mixed and set aside.

[0078] (2) In vitro blood adsorption ability test

[0079] Weigh 0.1g of the drug powder to be tested and place it in a 1.5mL centrifuge tube. At the same time, measure 0.5mL of anticoagulated blood and add it to the centrifuge tubes containing different drugs. Place them vertically on the laboratory workbench and start timing. After 30s, rotate the inverted centrifuge tube to observe whether the blood flows. Repeat the operation until the anticoagulated blood cannot flow and stop timing. Fig.12As shown in the results, β-SF-EA achieved complete adsorption of blood within two minutes, while other groups could not achieve this effect, indicating that the ability of β-SF-EA to adsorb blood was significantly better than the positive control Yunnan Baiyao and tranexamic acid, and was also significantly better than β-SF and EA monomers, indicating that β-SF and EA can synergistically enhance their effects.

[0080] (3) Test tube tilt coagulation test

[0081] Accurately weigh 5.0 mg of the drug powder to be tested and place it in a 10 mL test tube, spreading the powder as much as possible at the bottom of the test tube. Take 1 mL of anticoagulated blood and add it to the test tube, then add 0.2 mol·L -1 Add 25 μL of CaCl2 solution and mix again immediately, and start timing immediately. Let it stand for 1 minute, tilt the test tube every 30 seconds, and stop timing when the blood coagulates and stops flowing. Fig.13 It was observed that the complete blood coagulation time of the β-SF-EA group (2 minutes) was much shorter than that of the Yunnan Baiyao group (5 minutes), the tranexamic acid group (4 minutes 30 seconds), β-SF (5 minutes) and EA (>5 minutes), indicating that β-SF and EA can synergize. This experiment observed that β-SF-EA has a faster coagulation ability than other drugs.

[0082] (4) Blood rheology measurement

[0083] Whole blood viscosity is the result of friction between blood cells and plasma protein molecules when blood flows, and is the most important indicator in blood rheology. When blood viscosity increases, it means that blood flow is obstructed, and at the same time, the deformability of red blood cells decreases and the aggregation increases, the flow of blood into microvessels and capillaries decreases, and the passing capacity decreases. The method in Example 3 was used to measure the viscosity of blood after β-SF-EA acted on blood at 1·s -1 , 30·s -1 , 100·s -1 , 150 s -1 , 200·s -1 The results in Table 3 show that, regardless of the shear rate, β-SF-EA significantly increased the viscosity of whole blood (P<0.05), and was significantly better than the commercial chitosan hemostatic powder group (P<0.05). The commercial chitosan hemostatic powder in the control group was purchased from the instantaneous composite microporous polysaccharide hemostatic powder of Seikesaisi Biotechnology Co., Ltd., and its main active ingredient is chitosan.

[0084] Table 3 Comparison of whole blood viscosity between β-SF-EA and chitosan (n=3)

[0085]

[0086] *: Compared with the blank group, *P<0.05, **P<0.01, ***P<0.001; #: Compared with the commercial chitosan hemostatic powder group, #P<0.05, ##P<0.01, ###P<0.001.

[0087] (4) Blood coagulation index (BCI)

[0088] Prepare different masses of β-SF-EA (10, 20, 30, 40, 50 mg), place them flat in several 50 mL centrifuge tubes, take 0.1 mL of anticoagulated blood and gently drip it on the sample, then immediately drip 0.02 mL of 0.2 mol / L CaCl2 solution, gently add 25 mL of deionized water to the beaker after 5 minutes, centrifuge at 300 rpm for 5 minutes, then take out the solution, and measure its Abs value at a wavelength of 540 nm with an enzyme marker. Set up a control: add 0.1 mL of anticoagulated blood to a beaker, then add 25 mL of deionized water, and assume that the Abs value measured at the same wavelength is 100 as a reference value, then the coagulation index BCI is: BCI = 100 × A 样品 / A 对照 The BCI index is an indicator of the coagulation effect. The smaller the index, the better the coagulation effect. Fig.14 It shows that increasing the dosage (increasing the concentration in the same volume) will significantly reduce the blood coagulation index (BCI), which means that the coagulation effect is positively correlated with the dosage.

[0089] Example 12 Investigation of hemostatic effect

[0090] Male SD rats (about 250.0 g) were used to evaluate the hemostatic ability of β-SF-EA.

[0091] Rat tail amputation hemostasis experiment: SD rats were anesthetized by intraperitoneal injection of 1% sodium pentobarbital. 6 cm was measured from the end of the rat's tail, and the tail of the rat was cut with surgical scissors. 20 mg of sample powder (β-SF-EA, Yunnan Baiyao, tranexamic acid) was sprinkled on the wound immediately after bleeding, and the time was started from the bleeding.

[0092] Rat liver wound hemostasis experiment: SD rats were anesthetized by intraperitoneal injection of 1% sodium pentobarbital. The anesthetized rats were fixed in a supine position on the dissecting table, and a longitudinal incision was made along the midline of the abdomen to enter the abdominal cavity and expose the right lobe of the rat liver. The peritoneal fluid was blotted with clean gauze, and a parallel wound of about 2.0 cm long and 0.5 cm deep was made on the right lobe of the liver with a blade. After bleeding, the wound was immediately blotted with cotton that had been weighed in advance, and then 20 mg of sample powder (EA, β-SF, β-SF-EA, Yunnan Baiyao, tranexamic acid) was sprinkled on the wound surface, and the timing was started. The wound was first pressed with cotton for 30 seconds to observe whether it was bleeding. If bleeding continued, it was pressed with cotton for another 30 seconds and then observed. This was repeated until no obvious blood stains appeared on the cotton surface, which was considered successful hemostasis. The timing was stopped and the hemostasis time was recorded.

[0093] Rat thigh muscle trauma hemostasis experiment: SD rats were anesthetized by intraperitoneal injection of 1% sodium pentobarbital, and the anesthetized rats were fixed in a supine position on the dissecting table, and the leg hair was shaved with a rat hair scraper. After the inner thigh was disinfected with alcohol, a scalpel was used to cut a muscle wound about 3 cm long and 1 cm deep. The timer started when the wound was bleeding. After bleeding for 5 seconds, 20 mg of sample powder (EA, β-SF, β-SF-EA, Yunnan Baiyao, tranexamic acid) was sprinkled respectively, and the hemostatic effect was observed and the hemostatic time was recorded.

[0094] Fig.15 This is a rat tail amputation experiment. When β-SF-EA was placed on the wound, bleeding stopped quickly, and almost no blood was left on the filter paper. It can significantly promote hemostasis within 30 seconds; the blank group bled for more than five minutes, which lost statistical significance and was not listed in Figure B. As a control, the tranexamic acid group and the Yunnan Baiyao group required more than 4 times the time to stop bleeding, and the amount of bleeding was significantly higher than that of the β-SF-EA group (P<0.05).

[0095] Fig.16 This is a graph of the bleeding time of the rat liver and femoral artery. The femoral artery bleeding in the blank group exceeded five minutes, which lost statistical significance and was not included in the graph. Fig.16 It shows that β-SF-EA can significantly shorten the hemostasis time of the two models, and the hemostatic efficacy is significantly better than Yunnan Baiyao (P<0.05) and tranexamic acid (P<0.05), and is also significantly better than EA (P<0.05) and β-SF group (P<0.05), indicating that silk fibroin and ellagic acid have a synergistic effect, and the above results are consistent with the blood rheology and test tube tilting coagulation results in Example 11. It was observed in both rat bleeding models that β-SF-EA has a faster sedimentation rate in the blood than other drugs, and is easy to quickly settle to the bleeding site, while Yunnan Baiyao, tranexamic acid, and β-SF powders are lighter in texture and are more likely to float on the surface of whole blood and be washed away by the blood flow, thereby affecting their hemostatic effect.

[0096] Example 13 Safety Investigation

[0097] (1) Cell recovery

[0098] Take out the frozen LO2 cells and L929 cells, and gently shake them in a 37℃ water bath until they are completely thawed. In the clean bench, transfer the cell suspension in the cryopreserved tube to a cell culture bottle, and add 4mL of DMEM medium containing 10% fetal bovine serum to the culture bottle. Use a dropper to gently blow to evenly disperse the cells in the culture medium, and then place it in a cell culture incubator at 5% CO2 and 37℃ for culture. After 6 hours of culture, place the culture bottle in the clean bench after alcohol disinfection, remove the old culture medium, and add 4mL of culture medium again after washing, and continue to culture in the cell culture incubator.

[0099] (2) CCK8 quantification method

[0100] 0.2 mg of β-SF-EA and EA were respectively dissolved in 1 mL of DMSO, and gradient concentrations were set up.

[0101] Take the cells in the logarithmic growth cycle, wash them with PBS solution, add trypsin digestion solution to treat the cells into a suspended state, calculate the cell density with a cell counting plate, and calculate 1×10 per well. 5 After cells / mL were inoculated into 96-well plates, they were placed in a cell culture incubator and cultured for 24 hours. After the cells adhered to the wall, the culture medium was aspirated and washed twice with PBS. 100 μL of the experimental group: β-SF-EA and EA extracts, the blank group: DMEM culture medium containing 10% fetal bovine serum, and the positive group: paclitaxel extract were added to the 96-well plates inoculated with cells. Six parallel samples were set up for each group, and then placed in a 37°C, 5% CO2 cell culture incubator for 48 hours. The culture medium was aspirated, washed twice with PBS, and 100 μL of CCK8 solution (90 μL DMEM culture medium + 10 μL CCK8) was added. The plates were placed in an incubator and incubated in the dark for 30 minutes, and then the absorbance (OD) at 450 nm was detected with an enzyme reader. Six parallel samples were repeated at each time point, and the relative cell proliferation rate was calculated according to the following formula: Relative growth rate (RGR) % = OD 实验组 / OD 空白组 *100%. The cytotoxicity level is determined according to the cytotoxicity level in Table 4, where the positive control must not be lower than level 3. Cells with a level of 0-1 are qualified.

[0102] Table 4 Cell proliferation response grading standard

[0103]

[0104] We investigated the toxicity of β-SF-EA and EA on L929 cells and LO2 cells using CCK8 assay. Fig.17 As shown in the figure, the relative proliferation rate of all β-SF-EA groups was higher than 85%. According to the toxicity grading standard of ISO10993-1, the cytotoxicity of β-SF-EA was 0-1. At the same time, the addition of silk fibroin effectively improved the biocompatibility of ellagic acid. In summary, β-SF-EA does not affect cell proliferation and has good cell compatibility.

[0105] (2) Hemolysis test

[0106] Dilute 8mL of fresh rabbit blood with 10mL of normal saline. Put 20mgβ-SF-EA into a 50mL centrifuge tube, add 10mL of normal saline, and place in a 37℃ water bath for 10min. Then add 0.2mL of diluted rabbit blood, shake gently, and centrifuge at 1000rpm for 5min after a water bath for 60min. Take the supernatant and measure the absorbance at 540nm. The positive control group used 10mL of distilled water plus 0.2mL of rabbit blood, and the negative control group used 10mL of normal saline plus 0.2mL of rabbit blood. The operation method was the same. Each group was run in triplicate. The hemolysis rate was calculated as follows: Hemolysis rate (%) = (absorbance of the test sample - absorbance of the negative control) / (absorbance of the positive control - absorbance of the negative control) * 100%.

[0107] Different materials in direct contact with blood may cause red blood cells to rupture and produce hemolysis. The hemolysis test is to evaluate the hemolysis of the material by checking the hemoglobin concentration. After calculation, the hemolysis rate of β-SF-EA is 1.13±0.02% (Table 5). According to GB / T4233.2, a hemolysis rate of less than 5% is qualified. Therefore, the prepared β-SF-EA meets international standards.

[0108] Table 5 Hemolysis rate (n=3)

[0109]

[0110]

[0111] Example 14 Degradation Performance Investigation

[0112] A certain mass of β-SF-EA was weighed and placed in a PBS solution containing 0.1 μ / mL protease XIV, and incubated at 37°C. A PBS solution without protease XIV was used as a blank sample. The samples (n=3) were incubated in PBS solution and PBS solution containing 0.1 μ / mL protease XIV for 5, 10, 15, 20, 25, and 30 days. All degradation samples were replaced with fresh solutions at a fixed time every day. The degradation products were dried at 60°C, and the samples were weighed to a constant weight. The residual mass retention rate R MThe calculation formula is as follows: M / % = M dt / M i *100%, where M i is the initial mass, M dt is the mass preserved after t days, mg.

[0113] As a hemostatic agent used in vivo and in vitro, it is required to have good biodegradability. Ideally, in the early stage of wound healing, the hemostatic powder can firmly bond the tissues together to avoid cracking. It is best to degrade slowly. As the wound heals, the drug gradually degrades. Finally, the remaining drug components can be completely degraded after the wound heals and absorbed by the human body or excreted through metabolism. The degradation effect of β-SF-EA at 37°C is as follows Fig.18 As shown. It can be found that the degradation rate of β-SF-EA in PBS is slow, and the residual mass at 30 days is 90.11±3.51%. In the PBS solution containing protease XIV, the degradation effect of β-SF-EA can be roughly divided into two stages: the first stage (0-15 days), the degradation rate is slow in this stage, and the residual mass is 67.83±2.25% at 15 days; the second stage (15-30 days), the degradation rate begins to increase significantly, and the residual mass is 24.50±0.70% at 30 days, and most of it is degraded, which shows that it has good degradability.

[0114] Example 15 Preparation of silk fibroin vascular embolic agent loaded with polyhydroxyphenol compounds

[0115] Step (3) is added on the basis of Example 1 or 2: the silk fibroin composite loaded with polyhydroxyphenol compound obtained in step (2) is prepared by one of the following methods: emulsification dispersion method, phase separation coagulation method, supercritical fluid technology, electrostatic adsorption method, dry granulation method. The following is an example of a part of the preparation method:

[0116] (1) Emulsification dispersion method: a common preparation method for vascular embolic agents, which is to mix the drug with a polymer solution and then use emulsification technology to form microspheres or particles. For example, microspheres of polylactic acid (PLA) and polylactic acid-polyether copolymers can be prepared by this method.

[0117] (2) Phase separation coagulation method: Similar to the emulsification dispersion method, but mainly through physical phase separation to form microspheres, this method can control the particle size and release characteristics of the microspheres.

[0118] (3) Supercritical fluid technology: Use supercritical carbon dioxide to atomize the drug and polymer solution to form microspheres. This technology reduces the use of surfactants and is suitable for the preparation of biodegradable materials.

[0119] (4) Electrostatic adsorption method: The drug (such as bleomycin) is loaded onto drug-loaded microspheres with anionic groups through electrostatic action. This method is simple and easy to implement industrial production.

[0120] (5) Dry granulation method: Powdered raw materials are pressed into granules by physical means (such as compression and extrusion), which can be used to prepare vascular embolic agents with different properties.

[0121] Example 16 Preparation of silk fibroin vascular embolic agent loaded with polyhydroxyphenol compounds

[0122] Different from Example 15, the vascular embolic agent is prepared by an emulsification dispersion method, and the specific steps are as follows:

[0123] S1) adding paraffin wax and Span80 into a four-necked flask, stirring evenly, adding dropwise the polyhydroxyphenol compound-loaded silk fibroin complex and super-liquid iodized oil obtained in step (2), plugging the flask, opening the flask and continuing to stir to obtain a suspension;

[0124] S2) adding the suspension into a centrifuge tube and centrifuging it, taking out the centrifuge liquid and adding anhydrous ethanol, then washing it with petroleum ether and anhydrous ethanol, and centrifuging it after washing;

[0125] S3) adding ethanol overnight, removing the ethanol and drying, and grinding the dried product into a uniform powder to obtain a vascular embolic agent.

[0126] Examples 17 to 19 used ellagic acid as a model drug of polyhydroxyphenol compounds, and the vascular embolic agent prepared by the method in Example 16 was used for experiments.

[0127] Example 17 Physical Properties of Vascular Embolic Agents

[0128] (1) Swelling rate The swelling rate of the vascular embolic agent was measured by calculating the change in diameter before and after the swelling experiment. To evaluate the effect of pH and temperature on the swelling rate of the microspheres, the samples were immersed in PBS with different pH values ​​(1.0, 5.8 and 7.4) at 37°C, or immersed in PBS with different temperatures (4°C, 37°C and 60°C) at a speed of 100 rpm at a pH of 7.4. The swollen microspheres were taken out at certain time points to measure their diameters. The swelling rate of the microspheres was calculated according to the following formula: Swelling rate = (D t -D0) / D0*100%, where D0 is the initial diameter of the microsphere, D t is the diameter of the microsphere after swelling. Fig.19As shown in the figure, in the environment with pH values ​​of 1.0, 5.8 and 7.4, the swelling tendency of the microspheres showed a rapid swelling trend in the first 10 minutes and reached the maximum swelling rate at 20 minutes. At the same time, the swelling rate of the microspheres increased significantly with the increase of pH value. The swelling behavior of the microspheres at 4℃, 21℃ and 37℃ showed rapid swelling in the first 10 minutes and reached the maximum swelling degree at 20 minutes, indicating that the ambient temperature has a great influence on the swelling rate of the microspheres.

[0129] (2) In vitro degradation The in vitro degradation performance of the β-SF-EA vascular embolic agent was measured using the method described in Example 14. Fig. 20 As shown in the figure, the mass loss of the microspheres increased with the increase of incubation time. In the first 7 days, the microspheres degraded slowly with a degradation rate of 4.1%, and the degradation rate accelerated in the last 2 weeks. On the 21st day, the weight loss rate reached 20.8%. Based on this degradation trend, it can be predicted that the microspheres have good degradability.

[0130] Example 18 Hemostatic Effect Investigation

[0131] Interventional embolization hemostasis in rabbit renal injury bleeding model. Experimental groups: 24 New Zealand white rabbits (4.0-4.4kg) were randomly divided into a vascular embolic agent experimental group, an autologous thrombus control group, and a blank control group (normal saline), with 6 rabbits in each group. The embolic material of the autologous thrombus control group was prepared as follows: a 5mL syringe pre-loaded with 500U thrombin was used to extract 5mL of whole blood through the arterial sheath, and the thrombin was immediately mixed with the whole blood to form an autologous thrombus. The blank control group was injected directly into the target artery through a catheter without embolic material.

[0132] The anesthetized rabbit was placed on a rabbit board in a supine position, and the limbs and upper incisors were fixed with gauze strips. The inner side of the root of the right hind limb was the surgical field, and the skin was prepared and disinfected before draping. After subcutaneous local anesthesia with ropivacaine mesylate, the right femoral artery was exposed surgically, the artery was cut open and a 4F arterial sheath was inserted, and heparin calcium was administered at a dose of 100U / kg; then the laparotomy was performed to model renal injury and bleeding and to perform renal artery interventional embolization for hemostasis. The steps were as follows:

[0133] ① After opening the abdomen and finding the right kidney, the surrounding tissues and fat capsules of the kidney were freed and the kidney was fully exposed. ② A 4F guiding catheter was used to inject iodixanol injection through the right renal artery and perform angiography to obtain images of normal renal arterial distribution. ③ A 1.5 cm long and 0.6 cm deep wound was made in the renal parenchyma using a scalpel to simulate rupture and bleeding after right kidney injury. After modeling, angiography was performed again to obtain images of kidney injury and bleeding. ④ The front end of the 4F guiding catheter was placed at the end of the right renal artery. According to the experimental results of the effect of contrast agents on thrombin activity, a special "sandwich" delivery method was used to inject 1 mL of embolic material into the embolization site through the catheter (the "sandwich" delivery method: first fill the catheter with contrast agent, then push a certain amount of thrombus into the catheter, and then inject contrast agent). ⑤ The bleeding of the renal parenchyma incision after the release of the embolic agent was observed with the naked eye, and renal artery angiography was performed to determine whether the embolization hemostasis was successful; if the hemostasis was still not complete, the embolic agent was injected into the embolization target site through the catheter again until the hemostasis was complete. The total amount of embolic agent used during the operation and the time from the time the angiography confirmed the success of embolization to the time the renal incision completely stopped bleeding were recorded. ⑥ After the operation, the abdomen was closed, the arterial sheath was removed, the right posterior femoral artery was ligated, the skin and subcutaneous tissue were sutured, and the animals were sent back to the animal room for feeding and observation.

[0134] Fig.21 The results showed that the average time from the completion of embolic delivery to complete hemostasis of the renal parenchyma was 1.5±1min, the amount of vascular embolic agent used was 0.53±0.16mL (0.4mL-0.8mL), and the survival rate of animals reached 100% one week after surgery. The average time from embolization to complete hemostasis in the autologous thrombus control group was 1.8±1.5min, the average amount of thrombus used was 0.90±0.35mL (0.4mL-1.4mL), and the mortality rate of experimental animals within 6 hours after surgery reached 50%. The interventional embolization hemostasis of the blank control group was unsuccessful.

[0135] Example 19 Evaluation of the effect of application in adjuvant therapy of tumors

[0136] Establishment of VX2 rabbit ear intervention animal model: ① The cryopreserved VX2 tumor strain was revived in a 37℃ water bath and injected into the deep thigh muscle of the passaged rabbit. After two weeks of observation, the tumor strain grew satisfactorily in the rabbit hind limbs, and the animal was killed to remove the tumor. The tumor was minced into 0.5mm diameter and placed in culture medium for use. ② Adult female New Zealand white rabbits weighing 2.5-3.0 kg. The experimental rabbits were raised individually in rabbit cages for at least 5 days. After anesthesia by injection of 3% sodium pentobarbital (1mL / kg) into the ear vein, the hair on the auricle was shaved with scissors. The tumor tissue block was derived from the non-necrotic and well-vascularized VX2 tumor tissue of the passaged rabbit hind limbs. The fresh tumor tissue was cut into 1×1×3mm strips. The tumor tissue block was used within 2h and implanted into a small subcutaneous pocket with a 18-gauge coaxial introduction needle. The size of the rabbit auricle tumor was recorded regularly with a caliper. ③VX2 rabbit auricle intervention animal model embolization experiment: 3% sodium pentobarbital (1mL / kg) was injected into the ear vein of the rabbit for anesthesia. Then, the auricle was shaved and disinfected, and the skin was incised parallel to and slightly outside the distal central auricular artery. The artery of the tumor can be found under the illumination of a flashlight. 2% lidocaine solution was dripped locally to prevent arterial spasm. A 21G needle with an external catheter was inserted into the distal end of the central auricular artery, and the needle and catheter were fixed with elastic tape to prevent accidental displacement. Finally, 0.5mL of vascular embolic agent was injected into the ear artery of the experimental rabbit, and normal saline (0.5mL pH=7) was injected into the ear artery of the control group rabbit. The injection process and embolization effect were observed by X-ray. The rabbit was killed 1 hour after the injection. The size of the rabbit auricle tumor was recorded regularly with a caliper. The rabbit ear tumor was removed and CT scanned. The results are as follows Fig. 22 As shown, the liver tumors in each group showed an increasing trend, but the tumor growth rate in the group treated with embolization was significantly inhibited, and the tumor necrosis in the group treated with embolization was more obvious, most of which showed flake necrosis in the central area of ​​the tumor. Some rabbits had small flake necrosis around the tumor or in the normal left lobe of the liver.

Claims

1. A silk fibroin vascular embolic agent loaded with polyhydroxyphenol compounds, characterized in that: A vascular embolic agent is prepared from a silk fibroin complex loaded with a polyhydroxyphenol compound, wherein the silk fibroin complex loaded with a polyhydroxyphenol compound is prepared by self-assembly of a polyhydroxyphenol compound and a silk fibroin, wherein the silk fibroin is treated by a β-folding conformational transformation process, and the feed ratio of the polyhydroxyphenol compound to the silk fibroin is a mass ratio of <1:1; the vascular embolic agent is prepared by one of an emulsification dispersion method, a phase separation coagulation method, a supercritical fluid technology, an electrostatic adsorption method, and a dry granulation method.

2. The silk fibroin vascular embolic agent as claimed in claim 1, characterized in that: The polyhydroxyphenol compound is selected from one or more of resveratrol, quercetin, baicalein, kaempferol, lignans, curcumin, ellagic acid, chlorogenic acid, ferulic acid, caffeic acid, syringic acid, sinapinic acid, rutin, myricetin, magnolic acid, fisetin, puerarin, rhein, honeysuckle glycoside, proanthocyanidins, p-coumaric acid, vanillic acid, hesperidin, naringenin, luteolin, genistein, rhein, oleanolic acid, epigallocatechin gallate, acacia glycoside, tea polyphenols, epigallocatechin, salvianolic acid, gallic acid, pyrogallol, catechins, and tannic acid.

3. The silk fibroin vascular embolic agent as claimed in claim 2, characterized in that: The polyhydroxyphenol compound is a poorly soluble polyhydroxyphenol compound.

4. The silk fibroin vascular embolic agent as claimed in claim 3, characterized in that: The poorly soluble polyhydroxyphenol compound is selected from one or more of resveratrol, quercetin, baicalein, kaempferol, lignans, curcumin, ellagic acid, chlorogenic acid, ferulic acid, caffeic acid, syringic acid, sinapinic acid, rutin, myricetin, magnolic acid, fisetin, puerarin, rhein, honeysuckle glycosides, proanthocyanidins, p-coumaric acid, vanillic acid, hesperidin, naringenin, luteolin, genistein, rhein, oleanolic acid, and epigallocatechin gallate.

5. The silk fibroin vascular embolic agent according to claim 4, characterized in that: The poorly soluble polyhydroxyphenol compound is ellagic acid.

6. The silk fibroin vascular embolic agent according to claim 5, characterized in that: The feeding ratio of ellagic acid to silk fibroin is 1:2-1:16 by mass.

7. The silk fibroin vascular embolic agent according to claim 6, characterized in that: The mass ratio of ellagic acid to silk fibroin is 1:

4.

8. The method for preparing the silk fibroin vascular embolic agent according to any one of claims 1 to 7, comprising three steps: silk fibroin conformational transformation, self-assembly with a polyhydroxyphenol compound, and preparation of a vascular embolic agent: Step (1): preparing a silk fibroin solution by a process for transforming the silk fibroin conformation from an α-helix to a β-folded conformation, wherein the conformational change can be achieved by chemical or physical methods, wherein the chemical method comprises promoting the transformation by means of polyols, polylactic acid, metal ions, pH or hydroxypropyl methylcellulose, and the physical method comprises promoting the transformation by means of high temperature, hydration and pressure, ultra-low temperature placement, freeze drying, shear force, ultrasound Waves, vortexes, laser irradiation, and high-pressure carbon dioxide treatment promote the transformation; step (2): after the polyhydroxyphenol compound is dissolved or suspended, it is mixed with the silk protein solution obtained in step (1) and stirred to allow it to self-assemble, thereby obtaining a silk protein complex loaded with polyhydroxyphenol compounds; step (3): the silk protein complex loaded with polyhydroxyphenol compounds obtained in step (2) is prepared by one of the following methods: emulsification dispersion method, phase separation coagulation method, supercritical fluid technology, electrostatic adsorption method, and dry granulation method to form a silk protein vascular embolic agent loaded with polyhydroxyphenol compounds.

9. The preparation method according to claim 8, characterized in that: The step (1) uses polyol to promote the transformation of the β-folding conformation of silk fibroin.

10. The preparation method according to claim 9, characterized in that: The polyol is ethanol.

Citation Information

Patent Citations

  • Fibroin medical biological adhesive and preparation method thereof

    CN108744023A

  • Silk fibroin hemostatic gel as well as preparation method and application thereof

    CN115645597A

  • Silk fibroin styptic powder as well as preparation method and application thereof

    CN115779138A

  • Silk-based adhesives

    WO2017095782A1

  • Method to produce in SITU self-assembled multifunctional nanocomposite hydrogel and its uses thereof

    WO2022136666A1